2012
DOI: 10.1093/jxb/ers144
|View full text |Cite
|
Sign up to set email alerts
|

Cold acclimation and floral development in almond bud break: insights into the regulatory pathways

Abstract: In temperate fruit trees, seasonal dormancy and cold acclimation have a major impact on blooming time and, consequently, fruit production. To gain insight into the still unclear molecular processes underlying blooming, expression of genes putatively involved in the cold response was studied in almond (Prunus dulcis Mill.), which is the earliest fruit tree in the family Rosaceae to bloom. The transcript levels of two C-repeat binding factor (PdCBF) genes and one of their putative targets, PdDehydrin1 (PdDHN1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…Different studies evaluated the frost injury in almond trees, however, molecular processes involved in the cold response are poorly investigated in this plant [23]. Although, Barros et al [23] recently demonstrated the role of PdCBF2 in cold acclimation of almond, to our current knowledge, there is no study on the molecular responses of almond to frost stress.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies evaluated the frost injury in almond trees, however, molecular processes involved in the cold response are poorly investigated in this plant [23]. Although, Barros et al [23] recently demonstrated the role of PdCBF2 in cold acclimation of almond, to our current knowledge, there is no study on the molecular responses of almond to frost stress.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of TFs belonging to the CBF family has been well-documented as being related to cold response and acclimation in peach, almond, apricot, cherry, and Japanese apricot (Kitashiba et al, 2002; Owens et al, 2002; Tittarelli et al, 2009; Li et al, 2009; Barros et al, 2012a,b; Trainin et al, 2013; Zhang et al, 2013; Guo et al, 2014). CBF proteins belong to the CBF/DRE binding ( DREB ) sub-family of the Apetala2-ethylene responsive factor (AP2/ERF) (Nakano et al, 2006).…”
Section: Flowering Date Controlmentioning
confidence: 99%
“…These results were attributed to the great variation among CBF genes, which can explain the variation in cold tolerance among P. mume populations. Interestingly, CBF -specific CTR/DRE cis elements in promoters of peach PpDAM 5 and PpDAM 6 genes were also found, suggesting their association with a CBF-regulon (Barros et al, 2012b). …”
Section: Flowering Date Controlmentioning
confidence: 99%
See 2 more Smart Citations